2006
DOI: 10.1097/01.mpa.0000235307.04110.a2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Diabetes in Cynomolgus Monkeys With High-dose Streptozotocin

Abstract: (1) High-dose Zanosar STZ induced diabetes safely in cynomolgus monkeys without adverse effects. (2) A triphasic blood glucose response suggested the complete induction of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…IVGTTs, OGTTs, ASTs and MMTs were performed 8-35 days (median 11 days) after induction of diabetes. Immunohistochemical analyses of pancreatic sections from four diabetic monkeys showed <1% of insulin-positive cells compared with ∼70% of insulin-positive cells in healthy controls, as reported previously [16].…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…IVGTTs, OGTTs, ASTs and MMTs were performed 8-35 days (median 11 days) after induction of diabetes. Immunohistochemical analyses of pancreatic sections from four diabetic monkeys showed <1% of insulin-positive cells compared with ∼70% of insulin-positive cells in healthy controls, as reported previously [16].…”
Section: Methodssupporting
confidence: 87%
“…In this regard, recent data indicate that wild-type neonatal or adult pig islets can survive for weeks in monkey recipients [2,3]. One of these studies [3], as well as our own studies [4,16], were performed in cynomolgus monkeys. These Old World monkeys represent a good model for islet transplantation studies [3,7,36].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Blood glucose levels were measured at pre-STZ injection, and 6, 20, and 28 h post-STZ injection. Corroborating previous studies [25,27], a representative triphasic blood glucose response to STZ was observed in monkeys treated with 100 mg kg 1 (STZ 100) and 68 mg kg 1 (STZ 68) of STZ (7.5 mmol L 1 at 6 h post-STZ, followed by 1.5 mmol L 1 at 20 h post-STZ, and 8 mmol L 1 at 28 h post-STZ). However, the insulindependent monkey treated with 60 mg kg 1 of STZ (STZ 60-ID) did not exhibit the above mentioned blood glucose response.…”
Section: Resultssupporting
confidence: 79%